2022
DOI: 10.1093/plphys/kiac124
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose nonfermenting-1-related protein kinase 1 regulates sheath-to-panicle transport of nonstructural carbohydrates during rice grain filling

Abstract: The remobilization of non-structural carbohydrates (NSCs) reserved in rice (Oryza sativa) sheaths is essential for grain filling. This assimilate distribution between plant tissues and organs is determined by sucrose non-fermenting-1-related protein kinase 1 (SnRK1). However, the SnRK1-mediated mechanism regulating the sheath-to-panicle transport of NSCs in rice remains unknown. In this study, leaf cutting treatment was used to accelerate NSC transport in the rice sheaths. Accelerated NSC transport was accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 91 publications
1
16
0
Order By: Relevance
“…Hence, snrk1αa mutants were compromised in yield components as compared to the WT. These results corroborate recent reports of reduced plant height and reduced seed set in Os SnRK1αA knock-out plants grown in normal conditions [ 20 , 33 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, snrk1αa mutants were compromised in yield components as compared to the WT. These results corroborate recent reports of reduced plant height and reduced seed set in Os SnRK1αA knock-out plants grown in normal conditions [ 20 , 33 ].…”
Section: Resultssupporting
confidence: 92%
“…Lu et al [ 37 ] isolated T-DNA insertion lines of rice SnRK1αA_ LOC_Os05g45420 and SnRK1αC_ LOC_Os08g37800 and found that germination and seedling growth are impacted in snrk1αa but not in snrk1αc mutant. More recently, rice mutants in SnRK1αA were developed by CRISPR/Cas9 that were instrumental in deciphering the regulation of sugar homeostasis under normal conditions or starvation and translocation of starch from sheath to panicle during grain filling in rice [ 20 , 33 ]. However, this is the first time, to our knowledge, snrk1αb + snrk1αc double-mutants are reported.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the phenotypical and biochemical analyses presented in Hu et al (2022) offer insights in the process of grain filling in rice. SnRK1, an essential kinase for plant development and growth, was shown to play a critical role in NSC remobilization from sheaths to grain.…”
mentioning
confidence: 95%
“…In the current issue of Plant Physiology , Hu et al (2022) present a study on NSC remobilization during grain filling in Nipponbare, a rice cultivar with a sequenced genome. Using a detailed time-course analysis to measure multiple physiological and biochemical parameters during the period following anthesis, Hu et al found that the sheath is a major source of NSC for grain filling.…”
mentioning
confidence: 99%
“…It phosphorylates and inactivates key metabolic enzymes, such as HMG-CoA reductase, nitrate reductase, and sucrose phosphate synthase ( Sugden et al ., 1999 ), and is involved in regulating the expression of genes encoding α-amylase ( Laurie et al ., 2003 ; Lu et al ., 2007 ) and asparagine synthetase ( Baena-González et al ., 2007 ). The authors have previously shown SnRK1 to be required for the remobilization of non-structural carbohydrates in rice sheaths during grain filling ( Hu et al ., 2022 ), and it is also involved in the re-allocation of carbon in response to herbivory ( Schwachtje et al ., 2006 ). SnRK1 also promotes starch accumulation in grains and tubers through modulation of sucrose synthase and ADP-glucose pyrophosphorylase gene expression ( Kanegae et al ., 2005 ; McKibbin et al ., 2006 ) and ADP-glucose pyrophosphorylase redox activation ( Tiessen et al ., 2003 ).…”
mentioning
confidence: 99%